PENGARUH UKURAN BENIH DAN PEMAKAIAN PESTISIDA TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium Ascalonicum L) - Wajib Pandia; Sumatera Tarigan; Nani Kitti Sihaloho; Donatus Dahang; Ranto P. A Pintubatu (Universitas Quality, 2022)
Research on the effect of tuber size and use of pesticides on the growth and yield of red onion (Allium Ascalonicum L) has been carried out at the UPT Seed Parent Horticulture Kutagadung Berastagi, Berastagi District, Karo Regency, from April-June 2021. The aim of the study were to determine the optimal seed size for growth and production of red onion variety of Batu Ijo and to find out how much pesticide dose was recommended.The results showed that the best plant height influenced by tuber size was U3 (N 12) 21.8 cm and U1 20 cm. Meanwhile, the lowest was U0 of 16.2 cm. The average number of plants that were most affected by fusarium disease was P0, the treatment with the least amount of pesticide was 15.5 plants. On the contrary, the lowest average was found at the level of P3 treatment, which was only 1 plant. Disease occurs along with increasing doses of fungicides and pesticides Optimum pesticide levels are h P2 (3 g of fungicide + 3 ml of insecticide) which produced an average number of tubers of 4,208. The highest average number of tubers was found at U3 which was 5.85 and the lowest was at U0 2.56. U3 level (seed tuber size > 15 grams) is the optimum treatment level. The average production per sample is the largest in the treatment effect of U3 which is 35.89 gr and the lowest is at U0 (5.52 gr). The average production per plot of the effect of pesticide level was P3 857.3 g or 0.8573 kg and the lowest was P0 689.1 g or 0.6891 kg. The average production per plot of the effect of seed tuber size level was U3 1507.2 gr or 1.5072 kg and the lowest was U0 194.3 gr or 0.1943 gr. The average production of shallots per plot was found in the U3P3 treatment (1589 gr or 1,589 kg) and the lowest was at U0P0 (159.3 gr).